2003
DOI: 10.1038/sj.bjp.0705054
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐inflammatory actions of methotrexate are critically dependent upon the production of reactive oxygen species

Abstract: The mechanism of action by which methotrexate (MTX) exerts its anti‐inflammatory and immunosuppressive effects remains unclear. The aim of this study is to investigate the hypothesis that MTX exerts these effects via the production of reactive oxygen species (ROS). Addition of MTX (100 nM–10 μM) to U937 monocytes induced a time and dose dependent increase in cytosolic peroxide [peroxide]cyt from 6–16 h. MTX also caused corresponding monocyte growth arrest, which was inhibited (P<0.05) by pre‐treatment with N‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
99
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 60 publications
6
99
1
1
Order By: Relevance
“…Based on in vitro studies, it has recently been reported that methotrexate reduces intracellular glutathione concentrations, and this leads to reversible inhibition of macrophage and lymphocyte function (Phillips et al, 2003). Although this is an interesting hypothesis and the in vitro data reported in this article generally sup-166 port this conclusion, it is unlikely to explain the antiinflammatory actions of methotrexate in patients with rheumatoid arthritis since intracellular glutathione levels are reduced to well below the methotrexate-induced levels already in the synovial cells of these patients (Maurice et al, 1997).…”
Section: Methotrexate Alters Cellular Redox Statementioning
confidence: 99%
“…Based on in vitro studies, it has recently been reported that methotrexate reduces intracellular glutathione concentrations, and this leads to reversible inhibition of macrophage and lymphocyte function (Phillips et al, 2003). Although this is an interesting hypothesis and the in vitro data reported in this article generally sup-166 port this conclusion, it is unlikely to explain the antiinflammatory actions of methotrexate in patients with rheumatoid arthritis since intracellular glutathione levels are reduced to well below the methotrexate-induced levels already in the synovial cells of these patients (Maurice et al, 1997).…”
Section: Methotrexate Alters Cellular Redox Statementioning
confidence: 99%
“…It has been demonstrated also that a synthetic analogue of prostaglandin E 1 prevents the production of ROS in the intestinal mucosa of MTX treated rats [34]. Finally, Phillips et al reported that ROS generation by MTX plays an important role in cytostasis of monocytes and cytotoxicity in T-cells [30].…”
Section: Introductionmentioning
confidence: 97%
“…Various cytokines [29,30] and free radicals including ROS play a crucial role in the inflammatory and immunity processes involved in rheumatoid arthritis (RA) [31]. The earliest evidence for pro-oxidant properties of MTX was presented by Gressier et al [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 MTX is a cytotoxic agent used in the treatment of leukaemia and various malignancies, as well as in non-neoplastic diseases such as psoriasis, rheumatoid arthritis and as anti-inflammatory and immunosuppressive agent. [1][2][3] Earlier studies have revealed that MTX is converted mainly to metabolites connected to glutamate (MTX-glu) in cells and tissues. 4 The complex so formed is referred to as polyglutamated forms which is responsible for most biochemical activities of MTX.…”
Section: Introductionmentioning
confidence: 99%